Beckett, Censorship and the Problem of Parody - Seán Kennedy (Estudios Irlandeses, 2019)
In a forceful critique of previous scholarship, Lloyd (Meadhbh) Houston discerns evidence of “sectarian eugenicism” in Beckett’s writings. It is a startling claim, and there are problems to it. In particular, I suggest, Houston ignores the issue of tone: Beckett’s use of parody. Responding to Houston’s critique, I offer some thoughts on eugenicism, sectarianism and misogyny in Murphy and First Love. The aim is not to exculpate Beckett from all charges of prejudice, only to complicate issues of complicity in a theocratic hetero-patriarchal society.